Prototype of IoT-based Clothes Drying Control System - Jayakrista, Suriandi; Wowiling, Rolty Glendy (Journal of Computer Engineering, Electronics and Information Technology, 2024)
The recent climate change has caused instability in seasonal transitions, consequently complicating weather predictions especially in rainy seasons. This situation presents several challenges, particularly in the context of outdoor clothes drying, especially when the house is left empty or there is no one inside. Moreover, public clothes washers use the same place for different types of clothes and use chemicals that often damage clothes. This can be prevented by washing at home. Hence, there is a need for automated clothes drying device when rain detected. Our prototype utilizes a raindrop sensor, infrared thermometer MLX90614, and implements the Internet of Things (IoT) that employs a telegram bot for monitoring and control, thus enabling the avoidance of weather instability effects on clothes drying, ensuring clothes are dried automatically when it's not raining. Functional software testing results indicate the device operates effectively, though in hardware there are still issues with the stability of motor movement, which will be addressed in further research stemming from this article.